Access to Medical and Supportive Care for Rural and Remote Cancer Survivors in Northern British Columbia. Issue 3 (1st February 2014) - Fuchsia Howard, A.; Smillie, Kirsten; Turnbull, Kristin; Zirul, Chelan; Munroe, Dana; Ward, Amanda; Tobin, Pam; Kazanjian, Arminee; Olson, Rob
Abstract Background Rural cancer survivors (RCS) potentially have unique medical and supportive care experiences when they return to their communities posttreatment because of the availability and accessibility of health services. However, there is a limited understanding of cancer survivorship in rural communities. Purpose The purpose of this study is to describe RCS experiences accessing medical and supportive care postcancer treatment. Methods Interviews and focus groups were conducted with 52 RCS residing in northern British Columbia, Canada. The data were analyzed using qualitative content analysis methods. Results General Population RCS and First Nations RCS experienced challenges accessing timely medical care close to home, resulting in unmet medical needs. Emotional support services were rarely available, and, if they did exist, were difficult to access or not tailored to cancer survivors. Travel and distance were barriers to medical and psychological support and services, not only in terms of the cost of travel, but also the toll this took on family members. Many of the RCS lacked access to trusted and useful information. Financial assistance, for follow‐up care and rehabilitation services, was rarely available, as was appropriate employment assistance. Conclusion Medical and supportive care can be inaccessible, unavailable, and unaffordable for cancer survivors living in rural northern communities.